Mutagenesis in Rice: The Basis for Breeding a New Super Plant - Viana, Vívian Ebeling; Pegoraro, Camila; Busanello, Carlos; Costa de Oliveira, Antonio (Frontiers in Plant Science, 2019)
The high selection pressure applied in rice since its domestication thousands of years ago has caused a narrowing in its genetic variability. Therefore, obtaining new rice cultivars becomes a major challenge for breeders and developing strategies to the increase of genetic variability has demanded the attention of several research groups. Understanding mutations and their application has paved the way for advances in the elucidation of the rice genetic, physiological and biochemical basis of traits. Therefore, creating variability through mutations has grown to be among the most important tools to improve rice. The rice small genome size enabled the faster release of the higher quality sequence draft as compared to other crops. The move from structural to functional genomics has been possible due to an array of mutant databases, highlighting mutagenesis as an important player in this progress. Furthermore, due to the synteny among the Poaceae, other grasses can also benefit from these findings. Successful gene modifications have been obtained by random and targeted mutations. Also, following mutation induction pathways, techniques have been applied to identify mutations and the molecular control of DNA damage repair mechanisms in the rice genome. This review highlights findings in generating rice genome resources showing strategies applied for variability increasing, detection and genetic mechanisms of DNA damage repair.